Ellie's story : a dog's purpose novel - Cameron, W. Bruce (Dog's purpose, 2015)
A story about Ellie, a dog that has been trained for search and rescue since a pup, and her handlers, Jakob and Maya, who are lost in their own way, and how Ellie saves them also.